2012
DOI: 10.1002/dev.21051
|View full text |Cite
|
Sign up to set email alerts
|

Pupil and salivary indicators of autonomic dysfunction in autism spectrum disorder

Abstract: Dysregulated tonic pupil size has been reported in Autism Spectrum Disorder (ASD). Among the possible sources of this dysregulation are disruptions in the feedback loop between norepinephrine (NE) and hypothalamic systems. In the current study, we examined afternoon levels of salivary alpha-amylase (sAA, a putative correlate of NE) and cortisol (used to assess stress-based responses) in two independent samples of children with ASD. We found a larger pupil size and lower sAA levels in ASD, compared to typical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 88 publications
(125 reference statements)
5
70
2
Order By: Relevance
“…In the current study, we evaluated the effects of terbutaline (β 2 -agonist) on development of cardiac and hepatic noradrenergic innervation in contrast to the effects of isoproterenol (β 1 - and β 2 -agonist) and methoxamine (α 1 -agonist) during different developmental periods. We found evidence that β 2 -adrenoceptor stimulation during a critical developmental period leads to deficiencies in peripheral sympathetic noradrenergic innervation, providing a link to observations of autonomic dysfunction reported in ASD (Anderson et al, 2012; Fan et al, 2009; Witter et al, 2009). …”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…In the current study, we evaluated the effects of terbutaline (β 2 -agonist) on development of cardiac and hepatic noradrenergic innervation in contrast to the effects of isoproterenol (β 1 - and β 2 -agonist) and methoxamine (α 1 -agonist) during different developmental periods. We found evidence that β 2 -adrenoceptor stimulation during a critical developmental period leads to deficiencies in peripheral sympathetic noradrenergic innervation, providing a link to observations of autonomic dysfunction reported in ASD (Anderson et al, 2012; Fan et al, 2009; Witter et al, 2009). …”
Section: Introductionsupporting
confidence: 72%
“…Our earlier work detailed adverse effects of terbutaline on expression of postsynaptic adrenergic and cholinergic receptors in these same target tissues (Auman et al, 2001a, b; Slotkin et al, 2005), properties that would amplify presynaptic defects; and indeed, we identified parallel changes in both cardiac and hepatic function in response to sympathetic and parasympathetic stimuli (Auman et al, 2001a; Hou and Slotkin, 1989; Navarro et al, 1991; Slotkin et al, 2005). The present results are therefore relevant for outcomes of inappropriate terbutaline use in preterm labor, specifically pointing to the need to examine whether exposed children show autonomic dysfunction, as well as providing a contributory component to autonomic manifestations in ASD (Anderson et al, 2012; Fan et al, 2009; Hirstein et al, 2001; Witter et al, 2009). …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, 8-month-olds will show greater pupil dilation when presented with impossible events (Jackson & Sirois, 2009). Pupil responses in ASD and TD groups have been investigated by Anderson, Colombo and their colleagues (Anderson, Colombo, & Shaddy, 2006; Anderson & Colombo, 2009; Anderson, Colombo & Unruh, 2012). They found that tonic pupil size is significantly elevated in children with ASD.…”
Section: Two Theories Of the Asd Advantage In Visual Searchmentioning
confidence: 99%
“…A specific, often non-verbal group that may benefit from insights and use of pupillometry are individuals with Autism Spectrum Disorders (ASD). Indeed, recent years have observed features such as increased pupil diameter along with other indicators of autonomic dysfunction in autism spectrum disorders [80]. The pupil has also been associated with key features of autism such as empathy in adults [81] and children as young as two years old [82], and has specifically been shown to be decreased in response to social reward in autistic children [83] and positive information in Asperger’s disorder [84].…”
Section: Introductionmentioning
confidence: 99%